A 1030 nm single-frequency distributed Bragg reflector Yb-doped silica fiber laser. (21st September 2017) - Sun, Bo; Jia, Jing; Huang, Jin; Zhang, Xueqiang; Bai, Jintao
Abstract: We demonstrate a single-frequency fiber distributed Bragg reflector (DBR) laser operating at 1030 nm by using a 1.1 cm long commercially available highly Yb-doped silica fiber. The DBR fiber laser has a threshold pump power of 5 mW, and the maximum output power is over 160 mW with a slope efficiency of 27% relative to the launched pump power. The linewidth of the laser at 1030 nm is 6 kHz. With the aid of only a 5 cm long amplifier stage, the output power is scaled up to 306 mW with a slope efficiency of 51.5%.